Reducing the Clinical and Public Health Burden of Familial Hypercholesterolemia: A Global Call to Action - Representatives of the Global Familial Hypercholesterolemia Community; Wilemon, Katherine A; Patel, Jasmine; Aguilar-Salinas, Carlos; Ahmed, Catherine D; Alkhnifsawi, Mutaz; Almahmeed, Wael; Alonso, Rodrigo; Al-Rasadi, Khalid; Badimon, Lina; Bernal, Luz M; Bogsrud, Martin P; et al. (JAMA cardiology, 2020)
IMPORTANCE: Familial hypercholesterolemia (FH) is an underdiagnosed and undertreated genetic disorder that leads to premature morbidity and mortality due to atherosclerotic cardiovascular disease. Familial hypercholesterolemia affects 1 in 200 to 250 people around the world of every race and ethnicity. The lack of general awareness of FH among the public and medical community has resulted in only 10% of the FH population being diagnosed and adequately treated. The World Health Organization recognized FH as a public health priority in 1998 during a consultation meeting in Geneva, Switzerland. The World Health Organization report highlighted 11 recommendations to address FH worldwide, from diagnosis and treatment to family screening and education. Research since the 1998 report has increased understanding and awareness of FH, particularly in specialty areas, such as cardiology and lipidology. However, in the past 20 years, there has been little progress in implementing the 11 recommendations to prevent premature atherosclerotic cardiovascular disease in an entire generation of families with FH. OBSERVATIONS: In 2018, the Familial Hypercholesterolemia Foundation and the World Heart Federation convened the international FH community to update the 11 recommendations. Two meetings were held: one at the 2018 FH Foundation Global Summit and the other during the 2018 World Congress of Cardiology and Cardiovascular Health. Each meeting served as a platform for the FH community to examine the original recommendations, assess the gaps, and provide commentary on the revised recommendations. The Global Call to Action on Familial Hypercholesterolemia thus represents individuals with FH, advocacy leaders, scientific experts, policy makers, and the original authors of the 1998 World Health Organization report. Attendees from 40 countries brought perspectives on FH from low-, middle-, and high-income regions. Tables listing country-specific government support for FH care, existing country-specific and international FH scientific statements and guidelines, country-specific and international FH registries, and known FH advocacy organizations around the world were created. CONCLUSIONS AND RELEVANCE: By adopting the 9 updated public policy recommendations created for this document, covering awareness; advocacy; screening, testing, and diagnosis; treatment; family-based care; registries; research; and cost and value, individual countries have the opportunity to prevent atherosclerotic heart disease in their citizens carrying a gene associated with FH and, likely, all those with severe hypercholesterolemia as well.
Keywords: směrnice pro lékařskou praxi jako téma; Global Health; Public Health; osobní újma zaviněná nemocí; hyperlipoproteinemie typ II; Practice Guidelines as Topic; Humans; veřejné zdravotnictví; Hyperlipoproteinemia Type II; celosvětové zdraví; lidé; Cost of Illness